Bilateral diaphragm paralysis after simultaneous cardiac surgery and Nuss procedure in the infant - Yuichi Tabata; Hikoro Matsui; Takahiko Sakamoto; Masahiko Noguchi (Elsevier, 2015)
The case of a 15-month-old boy with bilateral diaphragm paralysis after simultaneous cardiac surgery for tetralogy of Fallot, and Nuss procedure for pectus excavatum, is presented. Extubated one day after his first operation, the boy suffered severe respiratory distress soon after, due to bilateral diaphragmatic paralysis. Diaphragm paralysis restricted abdominal respiration, while thoracic respiration was inhibited by metallic bar after the Nuss Procedure, which combined prevented extubation for 47 days. Thoracoplasty, such as the Nuss Procedure, should not be performed simultaneously with cardiac surgery because abdominal and thoracic respiration can be restricted in infants, causing prolonged, severe, post-surgical respiratory failure.